DERMATOGLYPHICS: A PRESCRIPTION INSTRUMENT IN SPORTS (Fiep Bulletin - online, 2012)
According to the new sports training paradigm, athletes’ thorough genetic identification is applied to determine the best strategy for the development of their athletic potential. For this purpose, dermatoglyphics is a high technology tool that uses fingerprint analysis characterized as a wide spectrum genetic marker to identify the athlete’s physical qualities and deficiencies. The type of muscular fiber also features a high correlation rate with inherited physical characteristics. Based on dermatoglyphic results, the coach and the athlete can improve the long- and middle-run training schedule.The radar graphics devised by Fernandes Filho is an important instrument for training prescription. It makes it possible to identify the athletes’ or the team’s ideal moment, with their strong or weak performance points.In this work, the results of the study accomplished by Silva Dantas (2004) are presented in graphic style, and they illustrate the dermatoglyphic profile of basic, “somatotype” physical qualities for indoor soccer players at high, middle and low performance levels.According to the paper, there are several studies about the dermatoglyphic profile in Brazil, including activities such as volleyball, karate, boxing, “vale tudo” free style wrestling, Olympic gymnastics, handball, triathlon, field soccer, sand soccer and indoor soccer, body board, surf, track and field and others, results of which were continuously illustrated in a work table.
Keywords: dermatoglyphics; graphics radar